1) х² - 9х+14 = 0
Выделим полный квадрат: х² - 9х+14 = х² - 2*4,5х + 4,5² - 4,5² +14 =
= (х - 4,5)² - 20,25 + 14 = (х - 4,5)² - 6,25 = (х - 4,5)² - 2,5² =
= (х - 4,5 - 2,5)(х - 4,5 + 2,5) = (х - 7)(х - 2) => уравнение имеет вид:
(х - 7)(х - 2) = 0
х - 7 = 0 или х - 2 = 0
х = 7 или х = 2
ответ: 2; 7.
2) х²+5х - 14 = 0
Выделим полный квадрат: х²+5х - 14 = х² + 2*2,5х + 2,5² - 2,5² - 14 =
= (х + 2,5)² - 6,25 - 14 = (х + 2,5)² - 20,25 = (х + 2,5)² - 4,5² =
= (х + 2,5 - 4,5)(х + 2,5 + 4,5) = (х - 2)(х + 7) => уравнение имеет вид:
(х - 2)(х + 7) = 0
х - 2 = 0 или х + 7 = 0
х = 2 или х = -7
ответ: 2; - 7.
1) х² - 9х+14 = 0
Выделим полный квадрат: х² - 9х+14 = х² - 2*4,5х + 4,5² - 4,5² +14 =
= (х - 4,5)² - 20,25 + 14 = (х - 4,5)² - 6,25 = (х - 4,5)² - 2,5² =
= (х - 4,5 - 2,5)(х - 4,5 + 2,5) = (х - 7)(х - 2) => уравнение имеет вид:
(х - 7)(х - 2) = 0
х - 7 = 0 или х - 2 = 0
х = 7 или х = 2
ответ: 2; 7.
2) х²+5х - 14 = 0
Выделим полный квадрат: х²+5х - 14 = х² + 2*2,5х + 2,5² - 2,5² - 14 =
= (х + 2,5)² - 6,25 - 14 = (х + 2,5)² - 20,25 = (х + 2,5)² - 4,5² =
= (х + 2,5 - 4,5)(х + 2,5 + 4,5) = (х - 2)(х + 7) => уравнение имеет вид:
(х - 2)(х + 7) = 0
х - 2 = 0 или х + 7 = 0
х = 2 или х = -7
ответ: 2; - 7.
2)√(75*12)=√(25*3*3*4)=5*3*2=
3)√(72*32)= √(36*2*2*16) =6*2*4=
4)√(45*80)=√(9*5*5*16)=3*5*4 =
5)√(2,5*14,4)=√((25/10)(144/10)=√(25*12*12/100)=5*12:10=
Перемножить получившиеся числа самостоятельно не составит труда.